Royal Jelly and 10-Hydroxy-2-Decenoic acid activate autophagy through mTOR/ULK1 pathway to improve cognitive function in diabetic mice - Lu Xiu; Rongguang Ge; Siyu Lu; Linwei Li; Wenqi Huang; Guojun Du; Zengli Zhang; Jie Zhang; Zhongxiao Wan; Jie Chang (Journal of Functional Foods)
Diabetes, a ruthless chronic metabolic disorder, is increasingly considered to jeopardize global well-being over the decades. Royal jelly (RJ) is a complex natural product secreted by worker bees containing a unique fatty acid known as 10-hydroxy-2-decenoic acid (10-HDA). This study aimed to verify the protective effect on cognitive function of RJ and 10-HDA in diabetic mice and explore the underlying mechanism. Briefly, our animal experiment results suggested that 10-HDA had a significant hypoglycemic effect and improved cognitive performance. Through western blotting, RJ and 10-HDA intervention notably increased Atg7, Atg16L1, Beclin-1, Atg5, Atg12, Atg3, and LC3-II expression and decreased p62 expression. Meanwhile, decreased mTOR expression and increased ULK1 expression were also observed in the 10-HDA intervention group. In conclusion, 10-HDA can regulate mTOR/ULK1 pathway to activate autophagy to alleviate hippocampal damage, thereby improving cognitive function in mice with diabetes, which may provide a new option for real-world cognitive impairment management.